2013
DOI: 10.17659/01.2013.0058
|View full text |Cite
|
Sign up to set email alerts
|

Strangulated Gastric Volvulus

Abstract: Abstract:Gastric volvulus is a rare but potentially life-threatening condition. High index of suspicion is required in patients presenting with signs and symptoms suggestive of gastric outlet obstruction/Borchart's triad of epigastric pain and distension, retching or non-productive recurrent vomiting and difficulty in nasogastric tube insertion. We report a 14 year old young girl who presented in emergency department (ED) with signs of peritonitis and was later on diagnosed as acute gangrenous gastric volvulus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…Jethwani et al reported a case of strangulated gastric volvulus with diaphragmatic eventration in a young girl. Patient underwent partial gastrectomy with anterior gastropexy and repair of eventration [20].…”
Section: Discussionmentioning
confidence: 99%
“…Jethwani et al reported a case of strangulated gastric volvulus with diaphragmatic eventration in a young girl. Patient underwent partial gastrectomy with anterior gastropexy and repair of eventration [20].…”
Section: Discussionmentioning
confidence: 99%
“…CT and Magnetic Resonance Imaging are used less often but can be helpful in difficult cases [6]. On ultrasound, duplication cysts demonstrate an echogenic inner mucosal layer and a hypoechoic outer muscular layer.…”
Section: Discussionmentioning
confidence: 99%